Una Revisión de los sistemas de control aplicados a los simuladores de rodilla - Olvera Balderas, José Armando; Sosa-Savedra, Julio César; Ortega González, Rubén; Barceinas Sánchez, José Dolores Oscar (Ingeniería, 2022)
Context: Simulation and wear joint mechanisms have been studied and applied in knee biomechanical systems for more than 30 years. However, these have not been widely reported with regard to their control and/or automation strategies. This work aims to present the advances made in the technological development of the different platforms and models of knee simulators, based mainly on the Oxford and Stanmore platforms. Method: An exhaustive review of commercial equipment patents and scientific papers was conducted. The approach considered the kinematics and dynamics of the platforms and the control models actuators, interface, and tuning method used, as well as the tests conducted and the system error. Results: Biomechanical knee systems have not been widely reported, as far as their control and/or automation strategies are concerned, because many of them are commercial and patented. Some platforms are certified under certain standards but depend only on the controlled variable. In addition, a detailed comparison of the different types of existing platforms is presented, highlighting the hydraulic models with PID controllers. Conclusions: There is an area of opportunity to propose new design alternatives and/or control strategies for knee simulators. This, in turn, opens the possibility of developing new designs for other joints, as well as improved models of existing ones.